Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Pengelolaan Keuangan Tenaga Kerja Muda Di Sampit - Aziatin, Winda (Universitas Darwan Ali, 2024)
The increasing accessibility of financial products, combined with rising consumption trends, presents a unique challenge in financial management. This study explores how financial literacy and lifestyle influence the financial management of young workers in Sampit.Financial literacy involves understanding fundamental financial concepts, managing personal finances, and making informed financial decisions. Meanwhile, lifestyle reflects an individual's consumption habits and spending patterns. This research adopts a quantitative approach, focusing on young workers in Sampit. The sample is selected using purposive sampling, and data analysis is conducted through multiple linear regression. The results reveal that financial literacy does not significantly impact how young workers in Sampit manage their finances. However, lifestyle plays a crucial role, significantly influencing financial management behaviors. These findings suggest that consumption habits and spending patterns have a more substantial effect on young workers' financial conditions than their financial knowledge.